1991
DOI: 10.1212/wnl.41.10.1675
|View full text |Cite
|
Sign up to set email alerts
|

Inability to Sneeze as a manifestation of medullary neoplasm

Abstract: A young man with headache was unable to sneeze despite a strong sensory urge to do so. Magnetic resonance imaging revealed a cystic neoplasm in the medulla oblongata that presumably interrupted the efferent arc of the sneezing reflex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In humans, its topography remains uncertain, but cases of “inability to sneeze” have been observed after an inflammatory lesion of the rostral dorsolateral medulla [4] or an ischemic lesion of the lateral medulla [5]. Subsequent to this first step, an efferent (or respiratory) phase occurs with recruitment of a number of inspiratory and expiratory neurons [2]. Here we describe transient neurological symptoms following sneezing and finally revealing a cardiac papillary fibroelastoma.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In humans, its topography remains uncertain, but cases of “inability to sneeze” have been observed after an inflammatory lesion of the rostral dorsolateral medulla [4] or an ischemic lesion of the lateral medulla [5]. Subsequent to this first step, an efferent (or respiratory) phase occurs with recruitment of a number of inspiratory and expiratory neurons [2]. Here we describe transient neurological symptoms following sneezing and finally revealing a cardiac papillary fibroelastoma.…”
Section: Introductionmentioning
confidence: 95%
“…Sneezing is a protective physiological respiratory reflex that consists of a sequence of mouth closing, a single slow deep inspiration or series of inspiratory efforts, and then an explosive expiratory effort with closed glottis [1]; the consequence is increased intrapulmonary pressure [2]. However, this phenomenon can be modulated by voluntary cortical activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…9 The sneezing reflex may be divided in two phases. 3 The first is a nasal or sensitive phase, following stimulation of the nasal mucosa by chemical or physical irritants. The afferent pathways are through the olfactory and ethmoidal nerves, which converge in the putative ''sneezing centre'' in the medulla.…”
Section: Discussionmentioning
confidence: 99%
“…19 In the human, neither the existence nor the location of a sneezing centre has been confirmed up to now, although in the last few years various reports have suggested that structures located in the medulla participate in the human sneeze reflex. [3][4][5][6] Touch sensitive pathways from the face and nasal fossa are transmitted through large diameter myelinated fibres to the principal trigeminal sensory nucleus in the brain stem. When activated, free nerve endings-the nociceptor sense organsresult in the excitation of small diameter unmyelinated C afferent nerve fibres and provide nociceptive information to the trigeminal spinal tract nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show that afferent sensory nerve fibres from the nasal mucosa carried in the first two trigeminal nerves relay to the ventromedial spinal trigeminal tract and the adjacent pontine-medullary reticular formation ( Figure 1). 22 In humans too, the lateral medulla (close to the spinal trigeminal tract) is thought to be the likely location of the sneezing centre; evidenced by case reports of inability to sneeze in patients with lateral medullary syndrome or medullary neoplasm, [23][24][25] and a case report of paroxysmal sneezing in a patient with an infarct in the lateral medulla. 26 The efferent arc of the reflex involves an initial inspiratory phase then an expiratory phase where air is expelled at speeds of around 150 km/h, with the soft palate and uvula depressed to direct air through the nasal passages.…”
Section: The Sneezing Reflex and Unusual Triggers Thereofmentioning
confidence: 99%